Sesamum Technology: A Crop Diversification Alternative in Punjab - Kaur, Parminder; Singh, Narinderpal (Indian Journal of Extension Education, 2018)
Sesamum can play an important role in crop diversification in specific locations. Due to its good demand in local market there is a need to raise the Sesamum production through increase in area and productivity. To promote its new technology, Punjab Agricultural University, Ludhiana has conducted frontline demonstrations in Punjab during Kharif, 2016 for testing and popularizing Sesamum variety in Punjab Til No.2. The study based on 8 front-line demonstrations conducted in Amritsar district of Punjab reveals that the cultivation of Sesamum can be a viable alternative to paddy crop under scarce water resources in general and for small farmers, in particular, having lesser staying power to get assured irrigations. The sesamum variety recorded plant height (138.78 cm), no. of plants /m2 (52), no. of pods /plant (99.5), weight of 100 seeds (3.46 g), and no. of seeds/pod (100.5). The demonstrated technology recorded grain yield 5.50 q/ha which is 83.96 per cent higher yield than local check variety. The benefit-cost (B:C) ratio of this technology was 1.01. The insect pest and diseases were in the range of 0.25 to 1.50 and 0.25 to 2.50 per cent respectively. The technology gap, extension gap and technology index were 1.50 q ha-1, 2.55 q ha-1 and 21.42 per cent respectively. It was also observed that the productivity of Sesamum can be doubled with the help of available advanced technology.
Keywords: Front-line demonstration; extension gap; sesamum; technology gap; technology index